Changes in Attitudes Towards Migrations - Staničić, Frane (Migration and Central Europe: Challenges and Legal Responses, 2024)
Migrations are always active, and it is impossible to imagine a world without them. However, migrations in the past decade have become a leading problem globally, especially in the European Union (EU). The EU migration policy and its common asylum system are undergoing tectonic changes, as negotiations between the Member States pave the road to a new and sustainable EU migration policy. Moreover, the need to remake the Dublin procedure is obvious; consequently, the European Commission is trying to satisfy national differences among Member States on the one hand and the state interest-oriented approach on the other. In all this, it is crucial that the fundamental rights of migrants and asylum seekers not be overlooked.Keywords: migrations, legal regulation, perception, asylum, future regulation